The Australian Handbook for Careers in Psychological Science - Machin, Tony; Machin, Tanya; Jeffries, Carla; Hoare, Nancey (Open textbook library., 2022)
Despite psychology being one of the most popular undergraduate programs, students often report not knowing how training in psychology relates to careers. With chapters written by experts across Australia, this book explores just some of the many ways that students can apply their training in psychological science across a variety of careers and sectors.